2011
DOI: 10.1111/j.1601-5037.2011.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of work‐related musculoskeletal disorders among dental hygienists

Abstract: Objectives: Work-related musculoskeletal disorders (MSD) have been recognized as a considerable problem for the dental hygiene profession, with the majority of professionals reporting musculoskeletal pain. The aim of this study was to investigate which risk factors may help predict MSD among Australian dental hygienists. Methods: A modified version of the Standardised Nordic questionnaire was distributed to registered hygienists throughout Australia. Results: Logistic regression analysis revealed a variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 22 publications
1
77
0
5
Order By: Relevance
“…Moreover, LBP is also associated with escalating medical costs[1]. This condition often occurs as a result of cumulative trauma and can affect the bones, muscles and their attachments, as well as nerves and blood supply[3]. Considerable focus has been on back injuries and musculoskeletal disorders of workers in health care[35] and other industries[2, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, LBP is also associated with escalating medical costs[1]. This condition often occurs as a result of cumulative trauma and can affect the bones, muscles and their attachments, as well as nerves and blood supply[3]. Considerable focus has been on back injuries and musculoskeletal disorders of workers in health care[35] and other industries[2, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Since stress has several causes, it is not possible to establish a single way to prevent it or fight it. Associated to this, a certain working posture, maintained for a long time, may lead to continuous stress of most required muscles and may generate circulatory and metabolic disorders, in addition to causing pain or muscle discomfort 5 . The origin of musculoskeletal injuries is in general related to labor activities requiring excessive strength with hands, inadequate upper limbs (UULL) postures, repetitiveness of a same movement, mechanical compression of UULL structures and neighbor regions (shoulders, arms and hands) and not enough time to carry out a certain job 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Second, dental hygienists were only required to perform a single task (manual scaling) during data collection. Our decision to focus on scaling was based on previous research, which identified that dental hygienists in the United States spend upwards of 57% of the duration for each appointment scaling (Anton et al 2002;Bramson, Smith, and Romagnoli 1998;Yee, Crawford, and Harber 2005), and that scaling had the highest odds ratio as a predictor of MSD in dental hygienists (Hayes, Taylor, and Smith 2011). The final limitation was our choice to not include a backrest on the chair on which dental hygienists sat during data collection.…”
Section: Probabilitymentioning
confidence: 99%
“…More recent data have reported that dental hygienists spend between 54 and 57% of their time scaling (Anton et al 2002;Yee, Crawford, and Harber 2005). Scaling, or the debridement of plaque from the patient's teeth, had the highest odds ratio as a predictor of MSDs amongst dental hygienists (Hayes, Taylor, and Smith 2011). Scaling is performed using hand held instruments, Downloaded by [University of Tasmania] at 09:54 30 September 2015 forward, bend laterally and twist to the right to obtain either direct or indirect vision of the oral cavity (Liss et al 1995).…”
Section: Introductionmentioning
confidence: 97%